Reliability and component analysis of voltage-lift quadratic boost converter for xenon lamps. (2021) - Divya Navamani, J.; Vijayakumar, K.; Lavanya, A.; Jason Mano Raj, A.
Abstract: This paper deals with the material analysis of components used for the high gain dc-dc converter of High-Intensity Discharge (HID) lamps. The high gain dc-dc converter is derived by integrating voltage-lift cell with the quadratic boost converter. The derived topology's components are designed according to the chosen application. Optimum switching frequency is identified by the genetic algorithm to derive an efficient and optimum size converter for HID application. Different materials for inductor and capacitor are analysed to choose the right material for the right application. In addition to that, the reliability analysis of the proposed topology is carried out with the military handbook. Finally, the simulation of the topology is carried out in the nl5 simulator to prove the theoretical results.